Efectos ambientales de los efluentes de la planta de tratamiento de aguas residuales en el sector La Leonera, cantón Echeandía. año 2018 - Silva Mendoza, Edwin Ismael (2018)
The purpose of this research work was to evaluate the environmental effects of the effluents from the Wastewater Treatment Plant in the la Leonera del Cantón Echeandía sector, for which physical and chemical analyzes were carried out on samples of wastewater at the entrance and exit of the oxidation pools and surveys to the inhabitants of the area. Regarding the physical analysis of the effluents, there is no solid waste coming from the Treatment Plant, the pH is 6.73, the temperature is 23.25 ° C, dissolved solids 97.5mg / L, electrical conductivity 151μS / cm, turbidity of the samples download 6.42. The chemical parameters determined for nitrites 0.0035mg / L, nitrates 0.2065mg / L, total chlorine 0.085mg / L. copper 0.15mg / L, ammonia nitrogen 2.95mg / L, total hardness 347mg / L, COD 124.5mg / L, phosphates2.3mg / L; According to these parameters, the effluents comply moderately with the requirements demanded by the TULSMA Standard. The results of the interviews applied to residents of the la Leonera sector near the Wastewater Treatment Plant of the Canton Echeandía showed that there are unpleasant odors in the area, recurrence of respiratory diseases, 60% of the inhabitants said that there is a high environmental effect caused by the discharge of wastewater, 45% observed moderate changes in soil quality, while 55% indicated that agricultural activities were not affected by the effluents. Vester's matrix shows that the most critical variables are P2, P4, P5 and P6 with an average of 6.5 on the horizontal line and 6.5 on the vertical line, the passive problem corresponds to P3, while for P1 the result is indifferent. Keywords: Wastewater, Wastewater Treatment Plant